Editorial - Nain, Manjeet Singh (Indian Journal of Extension Education, 2021)
In order to build networks, deliberate on key ideas and bring to light insights on the challenges faced by extension personnel and researchers from private and public sectors for self-reliant India in wake of the pluralistic and innovative extension approaches has to be planned and collaborated for providing demand-driven and holistic services to farmers emerged as the best and sustainable extension mechanism. In the same wake the Indian Society of Extension Education took up the agenda in its National Seminar 2021 held at Banaras Hindu University, Varanasi during 4-6 October, 2021 where over 450 delegates deliberated on the major themes of seminar to bring out wonderful recommendations. Both the Organising Secretaries; Â Professor Basabaprabhu Jirli, Head , Department of Extension Education , IAS, BHU , Varanasi and team and Dr. Rashmi Singh, Secretary ISEE and Principal Scientist, ICAR-IARI, New Delhi along with her team in the leadership of President ISEE, New Delhi for meticulously planning the Seminar and implementing it in highly professional manner at a very short notice deserve applause . Itâ€™s my privilege to present the current issue (January-March, 2022) with coverage of 45 manuscripts from cross sectional authors and content reoriented in light of current situations. Â I am happy and extend my gratitude to the readers, authors and reviewers who have significantly contributed to this professional publication. As usual, it is again appealed to strive for higher level of professionalism in research conduction and reporting to compete with international standards. We, at our level are striving hard to make the Indian Journal of Extension Education (IJEE) at par with any other fully open access through online submission and management of its content. Although, publication with separate DOI to each article through Crossref and its inclusion by International indexing agencies has resulted in enhanced citations but still the citation in Scopus indexed journals is at lowest ebb which call for concerted efforts at all level. I extend my sincere thanks to all the authors for making valuable contributions. I also extend sincere thanks to all the expert members in the editorial board for their painstaking efforts. The support extended by Executive Council is duly acknowledged. The sincere thanks are to Dr. Mahesh Chander, Dr. H.K. De, Dr. Kalyan Ghadei, Dr. Gurdeep Singh, Dr. Jagjot Singh, Dr. D.K. Bose, Dr. Milind Ahire and Dr. V. K. J. Rao for timely reviewing the manuscripts. Special thanks are extended to the President, ISEE; Dr. U.S. Gautam, Secretary ISEE; Dr. Rashmi Singh, Treasurer, ISEE; Dr. B. K. Singh and Joint Secretary, ISEE; Dr. J. S. Malik for providing insightful thoughts and guidance in bringing out this issue. Dr. Bhanu P. Mishra, Vice President (Central Zone) deserves special thanks for making committed efforts at all stages of ISEE matters. (Manjeet Singh Nain)